2014
DOI: 10.1021/mz400575u
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Tail Regioregular Polythiazole Prepared via Kumada-Coupling Polycondensation

Abstract: Head-to-tail regioregular poly(4-alkylthiazoles) (C 9 -pTz, C 13 -pTz, alkyl = n-C9H19, n-C13H27) have been synthesized and spectroscopically and electrochemically characterized. The PTzs were obtained by transmetalation of 2-chloro-5-bromo-4-alkylthiazoles with i PrMgCl, followed by Kumada-coupling polycondensation. The polymers are largely insoluble in organic solvents but dissolve readily in the presence of, e.g., trifluoro acetic acid (TFA). Analyses of soluble trace fractions of the polymers gave num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…Comparison of cyclic voltammograms of PvTzHD with P3HT and C 13 ‐PTz. Data for P3HT and C 13 ‐PTz, adapted from reference *: internal reference ferrocene.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of cyclic voltammograms of PvTzHD with P3HT and C 13 ‐PTz. Data for P3HT and C 13 ‐PTz, adapted from reference *: internal reference ferrocene.…”
Section: Resultsmentioning
confidence: 99%
“…Both dppp and dppe based catalysts have been used to polymerize a broad range of monomers (Figures and 4). These include phenylenes, thiophenes, pyrroles, furans, selenophenes, tellurophenes, thiazoles, pyridines, fluorenes, thienopyrazines, dithienosiloles, carbazole and rylene diimides . In each of these cases, dramatic differences arise when exploring these different conjugated building blocks.…”
Section: Nickel Catalysts In Ctpmentioning
confidence: 99%
“…Pammer and McNeil have both explored 4‐substituted thiazoles, a related but more electron deficient five‐membered aromatic . Both research teams have noted dramatic changes in solubility for this monomer with the nitrogen atom in the 5‐membered ring, and a large siloxy side chain was necessary to achieve well‐defined polymers with narrow molecular weight distributions.…”
Section: Nickel Catalysts In Ctpmentioning
confidence: 99%
“…To further expand the scope of controlled polycondensation towards other electron-deficient building blocks, Pammer et al [29] recently presented the synthesis of head-to-tail regioregular poly(4-alkylthiazole) compounds via Kumadacoupling polycondensation of 2,5-dihalogenated-4-alkylthiazoles (Scheme 1). Subsequent analysis showed that the number average molecular weights (M n ) of poly(4-nonylthiazole) (C 9 -PTz) were 1.9-2.4 kDa with a Polydispersity Index (PDI) of about 1.1-1.3 and the M n of poly(4-tridecylthiazole) (C 13 -PTz) were 2.9-3.0 kDa (PDI1.1-1.2).…”
Section: Kumada Polymerizationmentioning
confidence: 99%
“…In comparison with the AB approach, the AA/BB approach of SPC is more popular, most likely because the monomers are easier to synthesize. For example, a high molecular weight copolymer comprised of alternating Scheme 1 Synthesis of C 9 -PTz and C 13 -PTz via Kumada polymerization [29]. benzothiadiazole (BTZ) and cyclopentadithiophene (CDT) units was synthesized by Müllen et al (M n =50 kDa, Scheme 2) [33].…”
Section: Suzuki-miyaura Polymerizationmentioning
confidence: 99%